Michał Borwicz, Apokryf pod tytułem Josl Rakower mówi do Boga - Borwicz, Michał; Polit, Monika (Zagłada Żydów. Studia i Materiały, 2007)
Michał Borwicz's text published in 1955 in “Almanach”, a Yiddish periodical, is the first serious historical and literary analysis, which proves that Josl Rakower Addresses God supposedly an authentic voice from the burning Warsaw ghetto, is apocryphal. It is also the first important, voice in a discussion regarding the need to clearly separate the hic et nunc Holocaust testimonies from literary texts on the Holocaust (written ex post).